Sudut Pandang Perencanaan dalam Pengembangan Pembelajaran - Dolong, M.Jufri (Inspiratif Pendidikan, 2016)
An educator’s or teacher’s planning of teaching programs should emphasize to the implementation of the learning process more smoothly and the results should be more effective. Therefore, there are some things that need to be considered in the planning of teaching programs. First, the curriculum is the first thing that needs attention in the teaching planning or the preparation of a teaching program. Second, the school condition is one of the important things need to be considered in teaching planning, especially for the availability of infrastructure and teaching aids. The means and tools of teaching support the implementation of the students’ learning activities. Third, the students’ ability and development; in preparing or planning a teaching, students’ also require more attentions in order to prepare teaching materials and method in accordance with students’ needs. In this case, the breadth and depth of teaching materials need to be tailored to the capabilities and the development of students. Fourth, the teacher; the circumstances and the ability of teachers really do not need to be considered because the teachers are required to have the ability in all matters pertaining to the implementation of education and teaching. If at any time they feel have shortcomings, it is a demand for them to learn and improve their competences in their capacity as a teacher and educator.